Nicotine addiction and attitudes survey at university of physical education - Gileva, O.B.; Rogov, O.S.; Polyak, D.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to survey nicotine addictions and attitudes at university of physical education. Methods and structure of the study. We run a questionnaire survey on a sample of students (n=133) majoring in 49.02.01 physical education discipline. The questionnaire survey was designed to group smokers and nonsmokers with/ without past smoking experiences, and test the groups for awareness of the nicotine addiction health risks, influences of different social/ environmental factors on their attitudes to smoking, motivations, etc. Results and conclusion. The sample was found to believe that the anti-smoking initiatives should include administrative restrictions on smoking; active campaigning to keep the students informed on the health risks and methods to quit smoking; and social climates with zero tolerance to smoke. The anti-smoking campaigners are recommended to prioritize the following three approaches: zero-tolerance social climates; efficient stress-coping strategies to help smokers; and administrative restrictions with no-smoking zones and regulations.